Otázky neolitu a eneolitu. 39. ročník. Brno, 9.-11. 9. 2020 Sborník abstraktů - Malíšková, Johana; Tóth, Peter (Masaryk University Press, 2020)
Title in English: Problems of the Neolithic and Eneolithic. 39th annual meeting. Brno, September 9-11, 2020: Abstract book. Presented publication is a collection of 40 abstracts of papers, which are conferred at the 39th annual meeting "Problems of the Neolithic and Eneolithic". The contributions are divided into four thematic blocks, which build on a long research tradition in Central Europe and reflect the new needs and directions of archaeology. Student session as a suitable platform for meeting with the next generation of archaeologists with professionals represents a separate block. The collection also includes invited lectures, which present new paradigmatic approaches to the interpretation of the archaeological record in the Neolithic and Eneolithic. The discussion session is devoted to currently intensively debated questions of settlement waste. This session concludes with memories of the most experienced researchers and their legacy for future generations of archaeologists.